PERLINDUGAN HUKUM BAGI ANAK KORBAN TINDAKAN BUYLLING DISEKOLAH - Prisko Yanuaris; Theresia Margareta; Wonga; Moi, Maria Carmela; Poma Susu, Valerianus A.; Sogho, Theobaldus S. (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
Bullying is an action that is not limited to physical torture and also the psychological development of the times makes it easier for someone to interact, so that someone, especially students, can easily carry out bullying, most of which is caused by promiscuity, lack of attention from parents and a free environment. Based on this, the problem in this case is what factors cause bullying and criminal sanctions against perpetrators of bullying among students. The research method used is Empirical Legal research using the applicable statutory approach. The results of this paper show that bullying is caused by internal factors originating from oneself and external factors originating from promiscuity in the surrounding environment. Criminal sanctions against perpetrators of bullying are subject to law under Article 80 paragraph (1) which is regulated in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection.